Comparison of opioid based and opioid free anaesthesia in short obstetrics and gynecological day care procedures: a prospective, randomized, and comparative study - Gejji, Jyoti; M. Joshi, Vishwas (International Journal of Research in Medical Sciences, 2025)
Background: There is scarce of data in resource-limited settings on comparing the feasibility, safety and efficacy of opioid based and opioid free anaesthesia in obstetrics and gynecological day care procedures. Methods: This is a prospective, randomized, comparative study consisting total of 100 patients. Patients were randomly allocated in to two groups viz. group CGA (control) received standard fentanyl-based general anaesthesia i.e., fentanyl l µg/kg IV bolus and propofol 2-2.5 mg/kg IV for induction and group OFA (intervention) received multimodal opioid-free anaesthesia (OFA) i.e., lidocaine 1 mg/kg IV over 5 min, ketamine 0.5 mg/kg IV bolus, paracetamol 1g IV (or 15 mg/kg if <50 kg), and propofol 2-2.5 mg/kg IV for induction. Results: Majority of the study subjects i.e., 28% were belonged to age group of 31-40 years in both group CGA and group OFA. BMI was majorly (70%) in the range of 18.5-24.9 kg/m2. The incidences of PONV were significantly (p=0.019) higher in control group (44%) as compared OFA group (22%). The composite hemodynamic stability score (p=0.005), time to first analgesic requirement (p<0.001), overall patient satisfaction mean score (p<0.001), recovery time (p<0.001), were significantly better in group OFA as compared to group CGA. The total complication rate observed was comparatively lower in in group OFA (2%) as compared to group CGA (12%). Overall incidences of side-effects were lower in group OFA (2%) as compared to group CGA (12%). Conclusions: Opioid-free anaesthesia regimen for a low-resource setting like our study setting has a promising success rate with reduced incidence of side-effects.